Exports, foreign direct investment and the costs of corporate taxation - Christian Keuschnigg (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper develops a model of a monopolistically competitive industry with extensive and intensive business investment and shows how these margins respond to changes in average and marginal corporate tax rates. Intensive investment refers to the size of a firm's capital stock. Extensive investment refers to the firm's production location and reflects the trade-off between exports and foreign direct investment as alternative modes of foreign market access. The paper derives comparative static effects of the corporate tax and shows how the cost of public funds depends on the measures of effective marginal and average tax rates and on the behavioral elasticities of extensive and intensive investment.
Keywords: D21; F23; H25; L11; L22; 330; exports; foreign direct investment; corporate taxation; extensive and intensive investment; effective tax rates; costs of public funds; Körperschaftsteuer; Multinationales Unternehmen; Direktinvestition; Monopolistischer Wettbewerb; Internationale Markteintrittsstrategie; Export; Excess Burden; Theorie